Three-dimensional computed tomography reconstruction for the diagnosis of traumatic urethral injuries - Labanca, Federico E.; Delnero, Patricia M.; Alonso, Verónica; Paganini, Raúl E. (Revista Argentina de Cirugía, 2026)
Retrograde urethrography is the gold standard method for the diagnosis of urethral injuries. In this setting, we report the use of computed tomography with intravenous injection and urethral administration of contrast medium and 3D reconstruction of the entire urethra. The definitive diagnosis of urethral injury was made. The advantage of this method is the possibility of making the diagnosis of traumatic injuries of the entire urinary tract, solid organs, hollow viscera and of the pelvic ring within a single imaging test, with high sensitivity and specificity, with no need to perform other complementary tests.